Comparative Dynamics of an Equilibrium Intertemporal Asset Pricing Model - Donaldson, John B.; Mehra, Rajnish (Review of Economic Studies, 1984)
This paper uses recursive competitive theory to develop a general equilibrium asset pricing model. In this framework all prices and rates of return are endogenously determined, thus enabling us to analyze the effects of changes in preferences, technological uncertainty, and expectations on the structure of security prices. In particular we focus on how the market risk premium varies with changes in the underlying economic environment, an issue which other asset pricing models have chosen not to address.